SISTEM AFFILIATOR BINARY OPTION PADA PLATFORM BINOMO DALAM PERSPEKTIF HUKUM ISLAM - Nabila Annisa Noor; Ahmad Sholikhin Ruslie (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
In the marketing plan is a medium that is mainly used by companies in order to increase product sales, various ways are carried out by companies to market the products they sell, either in print or digitally online. What is currently being done is one of them through the Affiliate Marketing strategy, which is a marketing strategy that uses digital media, the system provides a fee or commission from the services of someone who has marketed the company's products or services. The company will provide a commission if the product or service marketed by the affiliate is successfully sold by marketing and providing information through social media platforms. In a currency transaction or foreign exchange transaction which is fluctuating in nature based on dependence on the political conditions of the State as well as economically. In the era of globalization, a transaction has emerged that can be carried out in various ways, one of which is online transactions, buying and selling and taking advantage of the movement of foreign currencies which is currently more popular and has become part of the current trend, namely binary options trading. which is on the binomo platform from the point of view of Islamic law. In this research, the aim is to find out how the views of Islamic law regarding the binary options affiliate system are. This research uses normative legal research that uses the framework of finding the rule of law, principles of Islamic law, and legal doctrine used to answer a problem of legal issues being faced, in addition to collecting data used from library studies such as studying, reviewing and analyzing making notes from literature books, laws and regulations, newspapers, magazines, or relevant online media regarding the issues to be researched, namely: Binary Option Affiliate System on the Binomo Platform in the Perspective of Islamic Law